Factors That Influence Plumbing Learning Achievement of Grade X Students of Building Drawings Engineering, SMKN 3 Semarang - Tinov, Naufal; Widhana, Prizal (Universitas Negeri Semarang, 2020)
Learning achievement is one measure of success in teaching and learning. High and low grades achieved by students are influenced by internal and external factors. Internal factors that influence learning achievement are (1) Intelligence; (2) Interests; (3) Talent; and (4) Motivation. Whereas external factors are (1) School environment, and (2) Family environment. The problems examined are what kind of factors that influence and how much these factors affect. The population in this study was grade X students of Building Drawings Engineering of SMKN 3 Semarang. Total population was 71 using a sample of 61 students. The variables examined in this study are (1) Internal factors; (2) External factors; and (3) Learning achievements. Retrieval of data using (1) Observation techniques; (2) Documentation; (3) Questionnaire. Data analysis uses multiple regression analysis. The results of this study state that the factors that influence the plumbing learning achievement of grade X students of Building Drawings Engineering of SMKN 3 Semarang are internal factors consisting of (1) Intelligence; (2) Interests; (3) Talent; (4) Motivation; and (5) External factors which consist of (1) Family environment, and (2) School environment. The amount of influence of the internal and external factors on the plumbing learning achievement of students of Building Drawings Engineering class at SMKN 3 Semarang, partially the amount of the influence of internal factors is 26.9% and external factors is 19.5%. Simultaneously the amount of the influence of internal factors and external factors is 46.6%.